DEVELOPMENT OF A PREHISTORIC INDONESIAN HISTORY E-MODULE BASED ON BANYUWANGI LOCAL RESOURCES - I Kadek Yudiana; Sahru Romadloni (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
The objectives of this study are as follows: (1) to examine the procedure for developing an e-module for the National History of Indonesia: Prehistoric Era course based on local archaeological resources in Banyuwangi; (2) to develop and implement the e-module for the National History of Indonesia: Prehistoric Era course utilizing Banyuwangi’s archaeological heritage as a contextual foundation; (3) to determine the effectiveness of the e-module in supporting the teaching and learning process; (4) to provide students with contextual learning resources that enrich their understanding of historical material; and (5) to foster student motivation through the application of Student-Centered Learning and active learning approaches. The research method employed in this study is the ADDIE model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The population and sample of the study comprise 40 undergraduate students from the History Education Study Program, Faculty of Teacher Training and Education, Universitas 17 Agustus 1945 Banyuwangi, divided into small group and large group trials. The developed product was validated by media experts, material experts, and language experts. Following the validation process, the e-module was tested through several stages, namely (1) Preliminary Trial, (2) Main Field Trial, and (3) Operational Field Trial. The results indicate that the development of the E-Module on the National History of Indonesia: Prehistoric Era Based on Local Resources in Banyuwangi has a significant impact on enhancing students’ comprehension of prehistoric history, particularly in terms of content, language and textual clarity, visual presentation, and the overall learning process.